Modified polylactic acid-glycolic acid copolymer composite scaffold as well as preparation method and application thereof

By loading metal organic frame materials and ceramic materials on the polylactic acid-glycolic acid copolymer matrix, and introducing gradient pore structures and promoting tissue regeneration and repair drugs, the existing scaffolds have been solved, and the effects of rapid degradation, improved antibacterial performance and promoted cell growth are achieved.

CN119770728AActive Publication Date: 2025-04-08INST OF BIOLOGICAL & MEDICAL ENG GUANGDONG ACAD OF SCI

Patent Information

Application Number
CN202411952690.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing polylactic acid-glycopolymer-based scaffolds have problems such as slow degradation speed, hydrophobic surfaces that are not conducive to cell attachment, single function and complex preparation process.

Method used

Combining polydopamine as a carrier by loading metal organic frame materials and ceramic materials on the surface of the polylactic acid-glycolic acid copolymer matrix, and introducing gradient pore structures and promoting tissue regeneration and repair drugs into the scaffold.

Benefits of technology

The rapid degradation of the scaffold and drug release are achieved, the antibacterial performance and the induction of osteogenesis and differentiation of stem cells are enhanced, the cell attachment and growth environment is improved, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770728A_ABST
    Figure CN119770728A_ABST
Patent Text Reader

Abstract

The invention discloses a modified polylactic acid-glycolic acid copolymer composite material scaffold and a preparation method and application thereof, the polylactic acid-glycolic acid copolymer composite material scaffold has a porous structure, pores in the surface and the interior are communicated with each other, and the pore diameter from the surface to the interior is increased in a gradient manner; a metal organic framework material is loaded on the surface of the polylactic acid-glycolic acid copolymer composite material bracket. The printing stent of the modified polylactic acid-glycolic acid copolymer composite material stent has macroscopic macropores and microscopic pores at the same time, so that the surface roughness of the stent can be improved, the purpose of remarkably promoting stent cell adhesion is achieved, the specific surface area of the stent can be remarkably increased, and the stability of the stent is improved. The polylactic acid-glycolic acid copolymer is accelerated to degrade and release more acidic degradation products, so that the degradation of the polydopamine is accelerated, the release of the medicine embedded in the polydopamine is accelerated, and the problem of slow degradation of the polydopamine in vivo and in vitro is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials, and in particular relates to a modified polylactic acid-glycolic acid copolymer composite material bracket and a preparation method and application thereof. Background Art

[0002] In recent years, with the development of bone tissue engineering technology, prostheses prepared by tissue engineering have shown good cartilage repair effects, and there is hope that tissue engineering technology can be used to treat growth plate injuries. Cartilage tissue engineering generally includes scaffolds and active substances. The ideal bone tissue engineering scaffold should have an interconnected porous network structure to provide interconnected channels for cell migration, ion transport, and cell-to-cell interaction. Conventional technologies include foaming, sacrificial template method, freeze-drying method and casting method, etc. 3D printing is also called additive manufacturing technology. Due to its unique and significant advantages in high precision, personalized manufacturing and complex shape construction, 3D printing has penetrated into all walks of life, led innovation, and triggered changes in the global manufacturing industry. 3D printing obtains a three-dimensional entity by stacking raw materials layer by layer on a plane. The porosity and shape of the scaffold can be freely designed, which can well meet the needs of bone tissue engineering.

[0003] Polylactic acid-co-glycolic acid is a synthetic copolymer of polylactic acid and polyglycolic acid. It can be dissolved in a wide range of solvents and can be easily controlled to the desired size and shape. It has good biocompatibility and mechanical strength. 3D printed polylactic acid-co-glycolic acid scaffolds made by fused deposition method at a melting temperature of 197°C. However, during the research process, it was found that polylactic acid-co-glycolic acid has the disadvantages of degradation, acid production and lack of cell binding sites, and needs to be combined with other materials for modification research. The introduction of artificial materials by loading drugs, surface modification, physical doping, chemical grafting, etc. can supplement the characteristics that polylactic acid-co-glycolic acid does not have. By adjusting its mixed components, the advantages of each component can be maximized, and then the ideal parameter requirements of bone repair materials can be achieved. In addition, polydopamine microspheres have a certain drug loading capacity and can be used as a carrier of drugs and can be used in bone tissue engineering technology.

[0004] The existing technologies of bone tissue engineering scaffolds include: Literature [Xu Yingke. Characterization and biocompatibility study of 3D printed polycaprolactone / β-tricalcium phosphate scaffolds loaded with polydopamine microspheres [D]. Hainan Medical College, 2023. DOI: 10.27952 / d.cnki.ghnyx.2023.000017.] reported the preparation of polycaprolactone / β-TCP composite scaffolds loaded with polydopamine microspheres, which can be used as bone repair materials to promote bone repair; Literature [Dong Bo. Research on the repair effect of 3D printed composite scaffolds loaded with FK-16 on infected bone defects [D]. Jilin University, 2024. DOI: 10.27162 / d.cnki.gjlin.2024.005386.] reported that by synthesizing 3D printed hydroxyapatite / polycaprolactone scaffolds with sustainable release of FK-16, bone transplant materials that can be used to effectively repair infected bone defects were obtained. However, the polylactic acid-co-glycolic acid copolymer-based scaffolds and polydopamine drug-loaded particles prepared by the above-mentioned prior art generally have the following problems: 1) Polydopamine degrades slowly, and it is difficult to effectively release enough drugs to achieve antibacterial and bone-promoting effects; 2) The surface of the polylactic acid-co-glycolic acid copolymer scaffold is too hydrophobic, which is not conducive to cell adhesion and proliferation; 3) The components and functions of the material are relatively simple, and it is difficult to achieve good antibacterial and bone regeneration effects; 4) The preparation process is complicated and difficult to industrialize. Summary of the invention

[0005] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a modified polylactic acid-glycolic acid copolymer composite material scaffold. The second purpose of the present invention is to provide a method for preparing the above-mentioned modified polylactic acid-glycolic acid copolymer composite material scaffold. The third purpose of the present invention is to provide the application of the above-mentioned modified polylactic acid-glycolic acid copolymer composite material scaffold. The gradient pore structure scaffold of the present invention not only has good porosity and biocompatibility, antibacterial properties, and induces osteogenic differentiation of stem cells, but also can accelerate the release of antibacterial drugs, especially under infection conditions, and initiate the slow release of internally encapsulated drugs that promote tissue regeneration and repair, and is suitable for the repair and regeneration of bone tissue defects under infection.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a modified polylactic acid-glycolic acid copolymer composite material stent, comprising a polylactic acid-glycolic acid copolymer matrix, the surface of the polylactic acid-glycolic acid copolymer stent matrix is ​​loaded with a metal organic framework material, and the metal organic framework material is loaded with an antibacterial drug; the surface and the interior of the polylactic acid-glycolic acid copolymer stent matrix are distributed with interconnected pores, and the pores gradually increase from the surface of the polylactic acid-glycolic acid copolymer stent matrix to the inside; drug-loaded materials are distributed in the polylactic acid-glycolic acid copolymer stent matrix, and the drug-loaded materials include ceramic materials and drugs for promoting tissue regeneration and repair, and the surfaces of the ceramic materials and the drugs for promoting tissue regeneration and repair are coated with polydopamine.

[0008] The pores of the stent in the present invention gradually increase from the surface to the inside of the polycaprolactone stent matrix, forming gradient pores and a multi-level pore structure, wherein the internal pores of the polycaprolactone stent matrix refer to the pores formed by stacking between fibers (macroscopic pores, hundreds of microns), and the external pores of the polycaprolactone stent matrix are the pores formed on the fibers due to pore-forming technology (microscopic pores, several to tens of microns).

[0009] Preferably, the surface of the poly(lactic acid-co-glycolic acid) composite material has pores with a size of 1-100 μm.

[0010] Preferably, the ceramic material is selected from at least one of hydroxyapatite, bioglass, calcium silicate, calcium carbonate, calcium sulfate, tricalcium phosphate, octacalcium phosphate, and amorphous calcium phosphate.

[0011] Preferably, the metal organic framework material is a zeolite imidazolate framework material self-assembled by coordination of zinc ions and 2-methylimidazole.

[0012] Preferably, the drug promoting tissue regeneration and repair is selected from at least one of bone morphogenetic protein-2, bone morphogenetic protein-7, vascular endothelial cell factor, platelet-derived factor, curcumin, melatonin, alendronate sodium, naringin, resveratrol, dexamethasone, gentamicin sulfate, epidermal growth factor, fibroblast growth factor, keratinocyte growth factor, nerve growth factor, berberine hydrochloride, gentamicin, transforming growth factor, insulin-like growth factor, parathyroid hormone, growth hormone, interleukin, alendronate sodium, salmon calcitonin, zoledronic acid sodium, ibandronate sodium, strontium ranelate, and vitamin D.

[0013] Preferably, the molecular weight of the polylactic acid-glycolic acid copolymer is 10,000 to 100,000 Daltons.

[0014] The second aspect of the present invention provides a method for preparing the modified polylactic acid-co-glycolic acid composite material bracket of the first aspect, comprising the following steps:

[0015] S1, mixing the drug-carrying material, gluconolactone and polylactic acid-co-glycolic acid in a solvent to obtain a mixed solution, transferring the mixed solution to a mold and placing the mixed solution for a period of time to obtain a mixed material film; using the mixed material film as a printing material, 3D printing to obtain a scaffold with a gradient pore structure; after printing, immersing the scaffold with a gradient pore structure in water to remove gluconolactone and residual solvent;

[0016] S2. Reacting a scaffold having a gradient pore structure, 2-methylimidazole and a zinc source in water to obtain the modified polylactic acid-glycolic acid copolymer composite material scaffold.

[0017] Preferably, the method for preparing the drug-carrying material comprises the following steps: dispersing the drug for promoting tissue regeneration and repair and the ceramic material in an aqueous solution containing dopamine, and performing a mixing reaction to obtain the drug-carrying material.

[0018] More preferably, the mass ratio of the ceramic material, the regeneration and repair promoting drug and dopamine is (50-1000):(0.005-10):100.

[0019] Preferably, the mass ratio of the drug-carrying material to the polylactic acid-glycolic acid copolymer is (0.005-0.05):1.

[0020] Preferably, the mass ratio of the gluconolactone to the polylactic acid-glycolic acid copolymer is (0.5-3):1.

[0021] Preferably, the solvent is dichloromethane.

[0022] Preferably, the process conditions for 3D printing satisfy at least one of the following:

[0023] a) 3D printing uses a printing needle with a diameter of 0.15-0.4mm;

[0024] b) Printing and heating temperature: barrel 60~80℃, needle 60~90℃;

[0025] c) Fiber spacing 0.8mm×0.8mm; printing speed 8~17mm / s;

[0026] d) Air pressure is 320-400Kpa;

[0027] e) The height of the stent layer is 75-95% of the needle diameter;

[0028] f) The fiber orientation is "0-90°".

[0029] The fiber spacing refers to the distance between the mid-axes of adjacent fibers in the horizontal and vertical directions. The fiber orientation refers to the angle between the upper and lower layers of fibers. The support layer height refers to the layer thickness of the printed layers.

[0030] Preferably, in step S1, the mixing time is 30-100 hours.

[0031] More preferably, the mixing is performed under stirring conditions, wherein the stirring rate is 100 to 1000 rpm.

[0032] Preferably, the placement time is 40-100 hours.

[0033] Preferably, the film-forming condition of the mixed material film is volatilization film-forming.

[0034] Preferably, the mass ratio of the 2-methylimidazole to the zinc source is (18-60):1.

[0035] Preferably, the zinc source is zinc nitrate.

[0036] Preferably, step S2 specifically comprises the following steps: adding the scaffold with a gradient pore structure into an aqueous solution containing 2-methylimidazole for dispersion, slowly adding a zinc source for reaction, and washing and freeze-drying after the reaction to obtain a modified polylactic acid-glycolic acid copolymer composite material scaffold.

[0037] The third aspect of the present invention provides the use of the modified polylactic acid-glycolic acid copolymer composite material scaffold according to the first aspect in the preparation of a product for promoting bone tissue repair and regeneration.

[0038] The beneficial effects of the present invention are:

[0039] The invention provides a modified polylactic acid-glycolic acid copolymer composite material bracket, comprising a polylactic acid-glycolic acid copolymer composite material bracket; the polylactic acid-glycolic acid copolymer composite material bracket has a porous structure, wherein the pores on the surface and inside are interconnected, and the pore size increases gradually from the surface to the inside, so that the printed bracket simultaneously obtains macroscopic large pores (fiber gaps) and microscopic small pores (fiber surface holes), which can not only improve the surface roughness of the bracket, achieve the purpose of significantly promoting the adhesion of bracket cells, but also significantly improve the specific surface area of ​​the bracket, so that the polylactic acid-glycolic acid copolymer is accelerated to degrade and release more acidic degradation products, thereby accelerating the degradation of polydopamine and accelerating the release of drugs embedded therein, and solving the problem of slow degradation of polydopamine in vivo and in vitro.

[0040] The specific beneficial effects are as follows:

[0041] (1) The surface of the modified polylactic acid-co-glycolic acid composite material scaffold of the present invention is also loaded with a metal organic framework material, which can not only enhance the antibacterial properties of the polylactic acid-co-glycolic acid scaffold with a gradient pore structure, but also significantly induce osteogenic differentiation of stem cells, making it more suitable for regeneration and repair of bone defects. In addition, the polylactic acid-co-glycolic acid composite material scaffold of the present invention has microscopic pores, which provide more sites for the deposition of the drug-loaded metal organic framework material, which is conducive to further improving the biological activity of the scaffold.

[0042] (2) The modified polylactic acid-co-glycolic acid composite material scaffold of the present invention uses ceramic material as the scaffold forming material, which can enhance the mechanical strength of the scaffold and the drug-carrying material, making it suitable for bone repair. The modified polylactic acid-co-glycolic acid composite material scaffold of the present invention further disperses the drug for promoting tissue regeneration and repair inside the polylactic acid-co-glycolic acid copolymer, and compared with the conventional use of the adhesive effect of the polydopamine coating to adsorb and load the drug, the drug can be sustained and controlled to achieve a better therapeutic effect.

[0043] (3) The present invention provides a method for preparing the above-mentioned modified polylactic acid-glycolic acid copolymer composite material scaffold. The preparation method is simple and feasible. The use of gluconolactone as a pore-forming agent can make the scaffold have a gradient pore structure, so that the printed scaffold can simultaneously obtain macroscopic large pores (fiber gaps) and microscopic small pores (holes on the fiber surface). In addition, gluconolactone is easily soluble in water and can be easily eliminated after the reaction.

[0044] (4) The modified polylactic acid-glycolic acid copolymer composite scaffold of the present invention has great application potential in the preparation of products that promote bone tissue repair and regeneration. The surface-modified gradient pore structure scaffold has good porosity and biocompatibility, antibacterial properties, and the characteristics of inducing osteogenic differentiation of stem cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The release performance of the drug for promoting tissue regeneration and repair in vitro of the materials prepared in the examples and comparative examples;

[0046] Figure 2 The alkaline phosphatase activity of the scaffolds prepared in the examples and comparative examples. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.

[0048] Example 1

[0049] This embodiment provides a modified polylactic acid-glycolic acid copolymer composite material bracket, and the preparation method thereof is as follows:

[0050] S1. Dissolve / disperse 0.01 mg bone morphogenetic protein-2 and 300 mg bioglass in 100 ml weakly alkaline 1.5 mg / ml dopamine aqueous solution (pH=8.4), and stir at 400 rpm for 8 h to obtain drug-loaded bioactive ceramic@polydopamine particles.

[0051] S2, 10g of polylactic acid-co-glycolic acid (molecular weight: 30,000 Daltons) was dissolved in 50ml of dichloromethane, and then 10g of gluconolactone and 100mg of drug-loaded bioactive ceramics @ polydopamine particles were added, and mechanical stirring was performed at 500rpm for 48h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid solution. The solution was poured onto a glass culture dish and placed under ventilation for 72h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid film.

[0052] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 85℃, the needle temperature is 90℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 12mm / s, the fiber orientation is "0-90°", the air pressure is 320Kpa, and the scaffold layer height is 85% of the needle diameter, and the gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold is printed layer by layer. 30mg of gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold is soaked in 25ml of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold.

[0053] S4. The gradient pore structure scaffold is added into 28 ml of 12 mg / ml 2-methylimidazole aqueous solution, and 4 ml of 4 mg / ml zinc nitrate aqueous solution is added dropwise during stirring. After the reaction, the scaffold is washed and freeze-dried to obtain a gradient pore structure, ZIF8 surface-modified drug-loaded bioactive ceramic @ polydopamine / polylactic acid-glycolic acid copolymer scaffold.

[0054] Example 2

[0055] This embodiment provides a modified polylactic acid-glycolic acid copolymer composite material bracket, and the preparation method thereof is as follows:

[0056] S1. Dissolve / disperse 10 mg of gentamicin sulfate and 400 mg of hydroxyapatite in 100 ml of a weakly alkaline 1 mg / ml dopamine aqueous solution (pH=8.6), and stir at 600 rpm for 6 h to obtain drug-loaded bioactive ceramic@polydopamine particles.

[0057] S2, 10g of polylactic acid-co-glycolic acid (molecular weight: 30,000 Daltons) was dissolved in 20ml of dichloromethane, and then 20g of gluconolactone and 150mg of drug-loaded bioactive ceramics @ polydopamine particles were added, and mechanical stirring was performed at 600rpm for 48h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid solution. The solution was poured onto a glass culture dish and placed under ventilation for 60h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid film.

[0058] S3, put the film into the printing barrel, the needle diameter is 0.1mm, the barrel temperature is 95℃, the needle temperature is 85℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 360Kpa, and the scaffold layer height is 80% of the needle diameter, and the gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold is printed layer by layer. 30mg of gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold was soaked in 30ml of aqueous solution, and ultrasonicated at room temperature for 0.6 hours to obtain a gradient pore structure drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold.

[0059] S4. The gradient pore structure scaffold is added into 29 ml of 18 mg / ml 2-methylimidazole aqueous solution, and 3 ml of 3 mg / ml zinc nitrate aqueous solution is added dropwise during stirring. After the reaction, the scaffold is washed and freeze-dried to obtain a gradient pore structure, ZIF8 surface-modified drug-loaded bioactive ceramic @ polydopamine / polylactic acid-glycolic acid copolymer scaffold.

[0060] Example 3

[0061] This embodiment provides a modified polylactic acid-glycolic acid copolymer composite material bracket, and the preparation method thereof is as follows:

[0062] S1. Dissolve / disperse 5 mg of curcumin and 100 mg of octacalcium phosphate in 100 ml of a weakly alkaline 2 mg / ml dopamine aqueous solution (pH=8), and stir the mixture at 200 rpm for 12 h to obtain drug-loaded bioactive ceramic@polydopamine particles.

[0063] S2, 10g polylactic acid-co-glycolic acid (molecular weight: 100,000 Daltons) was dissolved in 100ml dichloromethane, and then 5g gluconolactone and 50mg drug-loaded bioactive ceramics @ polydopamine particles were added, and magnetic stirring was carried out at 300rpm for 36h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid solution. The solution was poured onto a glass culture dish and placed under ventilation for 48h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid film.

[0064] S3, put the film into the printing barrel, the needle diameter is 0.35mm, the barrel temperature is 110℃, the needle temperature is 105℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 5mm / s, the fiber orientation is "0-90°", the air pressure is 300Kpa, and the scaffold layer height is 75% of the needle diameter, and the gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold is printed layer by layer. 30mg of gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold was soaked in 9ml of aqueous solution, and ultrasonicated at room temperature for 1 hour to obtain a gradient pore structure drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold.

[0065] S4. The gradient pore structure scaffold is added into 36 ml of 9 mg / ml 2-methylimidazole aqueous solution, and 3 ml of 5 mg / ml zinc nitrate aqueous solution is added dropwise during stirring. After the reaction, the scaffold is washed and freeze-dried to obtain a gradient pore structure, ZIF8 surface-modified drug-loaded bioactive ceramic @ polydopamine / polylactic acid-glycolic acid copolymer scaffold.

[0066] Example 4

[0067] This embodiment provides a modified polylactic acid-glycolic acid copolymer composite material bracket, and the preparation method thereof is as follows:

[0068] S1. Dissolve / disperse 4 mg of dexamethasone and 800 mg of calcium carbonate in 100 ml of a weakly alkaline 0.8 mg / ml dopamine aqueous solution (pH=9), and stir at 800 rpm for 4 h to obtain drug-loaded bioactive ceramic@polydopamine particles.

[0069] S2, 10g polylactic acid-co-glycolic acid (molecular weight: 10,000 Daltons) was dissolved in 200ml dichloromethane, and then 30g gluconolactone and 200mg drug-loaded bioactive ceramics @ polydopamine particles were added, and magnetic stirring was performed at 1000rpm for 72h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid solution. The solution was poured onto a glass culture dish and placed under ventilation for 60h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid film.

[0070] S3, put the film into the printing barrel, the needle diameter is 0.45mm, the barrel temperature is 90℃, the needle temperature is 80℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 15mm / s, the fiber orientation is "0-90°", the air pressure is 380Kpa, and the scaffold layer height is 90% of the needle diameter, and the gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold is printed layer by layer. 30mg of gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold was soaked in 60ml of aqueous solution, and ultrasonicated at room temperature for 0.8 hours to obtain a gradient pore structure drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold.

[0071] S4. The gradient pore structure scaffold is added into 22 ml of 24 mg / ml 2-methylimidazole aqueous solution, and 2 ml of 13 mg / ml zinc nitrate aqueous solution is added dropwise during stirring. After the reaction, the scaffold is washed and freeze-dried to obtain a gradient pore structure, ZIF8 surface-modified drug-loaded bioactive ceramic @ polydopamine / polylactic acid-glycolic acid copolymer scaffold.

[0072] Comparative Example 1

[0073] This comparative example provides a method for preparing a ZIF8 surface-modified polylactic acid-co-glycolic acid scaffold, which is substantially the same as Example 1, except that gluconolactone is not used. The specific preparation method is as follows:

[0074] S1. Dissolve / disperse 0.01 mg bone morphogenetic protein-2 and 300 mg bioglass in 100 ml weakly alkaline 1.5 mg / ml dopamine aqueous solution (pH=8.4), and stir at 400 rpm for 8 h to obtain drug-loaded bioactive ceramic@polydopamine particles.

[0075] S2. Dissolve 10g of polylactic acid-co-glycolic acid (molecular weight: 30,000 Daltons) in 50ml of dichloromethane, add 100mg of drug-loaded bioactive ceramics @ polydopamine particles, and mechanically stir at 500rpm for 48h to obtain a drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72h to obtain a drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid film. .

[0076] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 85℃, the needle temperature is 90℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 12mm / s, the fiber orientation is "0-90°", the air pressure is 320Kpa, and the scaffold layer height is 85% of the needle diameter, and the drug-loaded bioactive ceramic @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold is printed layer by layer. 30mg of the drug-loaded bioactive ceramic @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold was soaked in 25ml of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain the drug-loaded bioactive ceramic @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold.

[0077] S4. The gradient pore structure scaffold is added into 28 ml of 12 mg / ml 2-methylimidazole aqueous solution, and 4 ml of 4 mg / ml zinc nitrate aqueous solution is added dropwise during stirring. After the reaction, the scaffold is washed and freeze-dried to obtain a ZIF8 surface-modified drug-loaded bioactive ceramic @ polydopamine / polylactic acid-glycolic acid copolymer scaffold.

[0078] The modified polycaprolactone composite material stent prepared in Comparative Example 1 has a relatively smooth surface, with occasional holes ranging from a few microns to tens of microns.

[0079] Comparative Example 2

[0080] This comparative example provides a method for preparing a polylactic acid-co-glycolic acid scaffold with a gradient pore structure, which is substantially the same as Example 1, except that: no surface modification of ZIF8 is performed. The specific preparation method is as follows:

[0081] S1. Dissolve / disperse 0.01 mg bone morphogenetic protein-2 and 300 mg bioglass in 100 ml weakly alkaline 1.5 mg / ml dopamine aqueous solution (pH=8.4), and stir at 400 rpm for 8 h to obtain drug-loaded bioactive ceramic@polydopamine particles.

[0082] S2, 10g of polylactic acid-co-glycolic acid (molecular weight: 30,000 Daltons) was dissolved in 50ml of dichloromethane, and then 10g of gluconolactone and 100mg of drug-loaded bioactive ceramics @ polydopamine particles were added, and mechanical stirring was performed at 500rpm for 48h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid solution. The solution was poured onto a glass culture dish and placed under ventilation for 72h to obtain a gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid film.

[0083] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 85℃, the needle temperature is 90℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 12mm / s, the fiber orientation is "0-90°", the air pressure is 320Kpa, and the scaffold layer height is 85% of the needle diameter, and the gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold is printed layer by layer. 30mg of gluconolactone / drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold is soaked in 25ml of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure drug-loaded bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold.

[0084] Comparative Example 3

[0085] This comparative example provides a method for preparing a polylactic acid-co-glycolic acid stent, which is substantially the same as Example 1, except that: the bioactive ceramic@polydopamine particles are not loaded with drugs. The specific preparation method is as follows:

[0086] S1. Dissolve / disperse 300 mg of bioglass in 100 ml of weakly alkaline 1.5 mg / ml dopamine aqueous solution (pH=8.4), and stir at 400 rpm for 8 h to obtain bioactive ceramic@polydopamine particles.

[0087] S2, 10g of polylactic acid-co-glycolic acid (molecular weight: 30,000 Daltons) was dissolved in 50ml of dichloromethane, and then 10g of gluconolactone and 100mg of bioactive ceramics @ polydopamine particles were added, and mechanical stirring was performed at 500rpm for 48h to obtain a gluconolactone / bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid solution. The solution was poured onto a glass culture dish and placed under ventilation for 72h to obtain a gluconolactone / bioactive ceramics @ polydopamine particles / polylactic acid-co-glycolic acid film.

[0088] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 85℃, the needle temperature is 90℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 12mm / s, the fiber orientation is "0-90°", the air pressure is 320Kpa, and the scaffold layer height is 85% of the needle diameter, and the gluconolactone / bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold is printed layer by layer. 30mg of gluconolactone / bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold was soaked in 25ml aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure bioactive ceramics @ polydopamine particles / polylactic acid-glycolic acid copolymer scaffold.

[0089] S4. The gradient pore structure scaffold is added into 28 ml of 12 mg / ml 2-methylimidazole aqueous solution, and 4 ml of 4 mg / ml zinc nitrate aqueous solution is added dropwise during stirring. After the reaction, the solution is washed and freeze-dried to obtain a bioactive ceramic @ polydopamine / polylactic acid-glycolic acid copolymer scaffold with a gradient pore structure and modified ZIF8 surface.

[0090] Comparative Example 4

[0091] This comparative example provides a method for preparing a polylactic acid-co-glycolic acid stent, which is substantially the same as Example 1, except that the drug-loaded polydopamine particles do not contain bioactive ceramics. The specific preparation method is as follows:

[0092] S1. Dissolve 0.01 mg of bone morphogenetic protein-2 in 100 ml of a weakly alkaline 1.5 mg / ml dopamine aqueous solution (pH=8.4), and stir at 400 rpm for 8 h to obtain drug-loaded polydopamine particles.

[0093] S2, 10g polylactic acid-co-glycolic acid (molecular weight: 30,000 Dalton) was dissolved in 50ml dichloromethane, and then 10g gluconolactone and 100mg drug-loaded polydopamine particles were added, and mechanical stirring was 500rpm for 48h to obtain gluconolactone / drug-loaded polydopamine particles / polylactic acid-co-glycolic acid solution. The solution was poured on a glass culture dish and placed under ventilation for 72h to obtain gluconolactone / drug-loaded polydopamine particles / polylactic acid-co-glycolic acid film.

[0094] S3. Put the film into the printing barrel, with a needle diameter of 0.25 mm, a barrel temperature of 85°C, a needle temperature of 90°C, a fiber spacing of 0.8 mm×0.8 mm, a printing rate of 12 mm / s, a fiber orientation of "0-90°", an air pressure of 320 Kpa, and a scaffold layer height of 85% of the needle diameter, and print the gluconolactone / drug-loaded polydopamine particles / polylactic acid-glycolic acid copolymer scaffold layer by layer.

[0095] S4. The gradient pore structure scaffold is added into 28 ml of 12 mg / ml 2-methylimidazole aqueous solution, and 4 ml of 4 mg / ml zinc nitrate aqueous solution is added dropwise during stirring. After the reaction, the scaffold is washed and freeze-dried to obtain a drug-loaded polydopamine / polylactic acid-glycolic acid copolymer scaffold with a gradient pore structure and ZIF8 surface modification.

[0096] Comparative Example 5

[0097] This comparative example provides a method for preparing a polylactic acid-co-glycolic acid stent, which is substantially the same as Example 1, except that it does not contain drug-loaded bioactive ceramic@polydopamine particles. The specific preparation method is as follows:

[0098] S1, 10g polylactic acid-co-glycolic acid (molecular weight: 30,000 dalton) is dissolved in 50ml methylene chloride, then 10g gluconolactone is added, mechanical stirring is 500rpm 48h, and gluconolactone / polylactic acid-co-glycolic acid solution is obtained. This solution is poured on a glass culture dish, placed under ventilation for 72h, and gluconolactone / polylactic acid-co-glycolic acid film is obtained.

[0099] S2, the film is placed in the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 85℃, the needle temperature is 90℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 12mm / s, the fiber orientation is "0-90°", the air pressure is 320Kpa, and the scaffold layer height is 85% of the needle diameter, and the gluconolactone / polylactic acid-co-glycolic acid copolymer scaffold is printed layer by layer. 30mg of gluconolactone / polylactic acid-co-glycolic acid copolymer scaffold is soaked in 25ml of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure polylactic acid-co-glycolic acid copolymer scaffold.

[0100] S3. The gradient pore structure scaffold is added into 28 ml of 12 mg / ml 2-methylimidazole aqueous solution, and 4 ml of 4 mg / ml zinc nitrate aqueous solution is added dropwise during stirring. After the reaction, the scaffold is washed and freeze-dried to obtain a polylactic acid-glycolic acid copolymer scaffold with a gradient pore structure and a ZIF8 surface modification.

[0101] Comparative Example 6

[0102] This comparative example provides a preparation method of a polylactic acid-co-glycolic acid stent, which is substantially the same as Example 1, except that it does not contain drug-loaded bioactive ceramic@polydopamine particles, gluconolactone, and ZIF8. The specific preparation method is as follows:

[0103] 10g of polylactic acid-co-glycolic acid copolymer (molecular weight: 30,000 Dalton) was placed in a printing barrel, with a needle diameter of 0.25mm, a barrel temperature of 85°C, a needle temperature of 90°C, a fiber spacing of 0.8mm×0.8mm, a printing rate of 12mm / s, a fiber orientation of "0-90°", an air pressure of 320Kpa, and a scaffold layer height of 85% of the needle diameter, and a polylactic acid-co-glycolic acid copolymer scaffold was printed layer by layer. 30mg of the polylactic acid-co-glycolic acid copolymer scaffold was soaked in 25ml of an aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain a polylactic acid-co-glycolic acid copolymer scaffold.

[0104] Experimental analysis

[0105] The scaffold materials prepared in the examples and comparative examples were evaluated for their performance as follows: Figures 1-2 and Tables 1 to 3.

[0106] 1. In vitro cytotoxicity evaluation

[0107] The prepared gel was evaluated and scored according to the requirements of GB / T 16886.5.

[0108] L929 mouse fibroblasts that had been cultured for 24 hours and were growing vigorously were digested and prepared to a density of 1.0×10 5 100 μL / mL was inoculated in a 96-well plate. After the cells grew into a monolayer, the original culture medium was removed and 100 μL of the test sample extract, blank control solution, positive control solution and negative control solution were added respectively, with 6 replicates in each group. After the addition of samples, the 96-well plate was placed in a 37°C, 5% CO2 incubator for 24 hours.

[0109] After 24 hours of culture, the original culture medium was aspirated, and 50 μL of MTT (1 mg / mL) was added to each well. The culture was continued for 2 hours. After the end, the supernatant was aspirated and 100 μL of 99.5% pure isopropanol was added to dissolve the crystals; the absorbance value was measured on an ELISA instrument with 570 nm as the main absorption wavelength and 650 nm as the reference wavelength to calculate the cell survival rate.

[0110] The cell viability was calculated according to the following formula: Cell viability (%) = 100 × OD 570e / OD570 b OD 570e It is the average optical density of the test sample or control sample extract.

[0111] OD 570b is the average optical density of the blank.

[0112] The experimental results are shown in Table 1:

[0113] Table 1 In vitro cell survival rate of the scaffolds prepared in the examples and comparative examples

[0114]

[0115] It can be seen from the in vitro cytotoxicity evaluation results of the examples and comparative examples (Table 1) that the composite gels prepared by the method of the present invention are non-cytotoxic.

[0116] 2. Hemolytic performance test

[0117] Blood was collected from the heart of healthy rabbits according to the amount of blood used in the experiment. For example, 10 mL of blood was collected, and 0.5 mL of potassium oxalate solution with a mass concentration of 20 g / L was added to prepare fresh anticoagulated rabbit blood. Take 8 mL of fresh anticoagulated rabbit blood and dilute it with 10 mL of sodium chloride injection with a mass concentration of 9 g / L. The test sample group was added with the test sample according to the extraction ratio, and then 10 mL of sodium chloride injection was added; 10 mL of sodium chloride was added to each tube of the negative control group; 10 mL of distilled water was added to each tube of the positive control group. Three tubes were operated in parallel for each group. After all the test tubes were placed in a constant temperature water bath at (37±1)℃ for 30 minutes, 0.2 mL of diluted rabbit blood was added to each test tube, gently mixed, and placed in a (37±1)℃ water bath for another 60 minutes. Pour out the liquid in the tube and centrifuge at 800g for 5 minutes. Aspirate the supernatant and transfer it to a cuvette, and measure the absorbance at a wavelength of 545 nm using a spectrophotometer. The absorbance of the test group and the control group is the average of the three tubes. The absorbance of the negative control tube should not be greater than 0.03; the absorbance of the positive control tube should be 0.8±0.3, otherwise the test should be repeated. Calculate according to the following formula: Hemolysis rate = (absorbance of the test group - absorbance of the negative control group) / (absorbance of the positive control group - absorbance of the negative control group) × 100%, the results are shown in Table 2:

[0118] Table 2 Hemolysis rate of materials obtained in Examples and Comparative Examples

[0119]

[0120] From the hemolysis rate evaluation results of the examples and comparative examples (Table 2), it can be seen that the hemolysis rate of the hydrogel prepared by the method of the present invention is less than 5%, and there is no hemolysis risk.

[0121] 3. In vitro drug release performance test

[0122] The in vitro drug release performance evaluation method is as follows: 500 mg of the product is immersed in 200 mL of PBS (pH = 7.4) in a constant temperature shaker at 37°C and 60 rpm, the test solution is collected regularly, and an equal amount of PBS is supplemented. The content of the therapeutic agent in the collected test solution is determined by high performance liquid chromatography (HPLC), and compared with the total amount of the therapeutic agent loaded in the product, the cumulative release rate of the therapeutic agent is calculated.

[0123] The results of in vitro drug release performance test are shown in Figure 1 , the release period of various drugs prepared by the stents in Examples 1 to 4 exceeds 5 weeks. Comparative Example 1 does not use gluconolactone, and its stent fiber does not contain a porous structure, and its drug release rate is lower than that of Example 1; Comparative Example 2 does not perform ZIF8 surface modification, and the burst release is significantly increased compared with Example 1, and the release rate is significantly accelerated, and the release is basically completed in 4 weeks. The drug-loaded polydopamine particles in Comparative Example 4 do not contain bioactive ceramics, and its drug release is close to that of Example 1.

[0124] 4. In vitro osteogenic differentiation test of preosteoblasts

[0125] The composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were irradiated and sterilized, and then immersed in DMEM basal culture medium at a concentration of 10 mg / mL, and placed in a 37°C shaker at 120 rpm for 24 hours. After the extraction, the mixture of the composite material and the culture medium was centrifuged at 1000 rpm and the supernatant was collected. The collected extracts were diluted 2 times with the corresponding DMEM culture medium, and finally 10% fetal bovine serum was added to obtain a conditioned medium.

[0126] MC3T3-E1 cells were plated at 1×10 5 The cells were inoculated in a 24-well plate at a density of 100 μg / mL. After 24 hours of adherent culture, the conditioned medium was replaced and cultured in an incubator at 37°C and 5% carbon dioxide atmosphere. The culture medium was replaced every 2-3 days. After 7 days of culture, the osteogenic differentiation performance of MC3T3-E1 cells was detected by the alkaline phosphatase secreted by them and measured by the pNPP method. The specific steps are as follows: After the cells were washed with PBS solution, they were immersed in a PBS solution containing 0.1 mol / L glycine, 1 mmol / L magnesium chloride and 0.05% Triton X-100 (octoxynol). After the cells were dissolved, the dissolved solution was evenly mixed with disodium p-nitrophenyl phosphate, and the mixed solution was placed at 37°C for 30 minutes. Subsequently, the mixed solution was added dropwise to a 96-well plate, and the absorbance of each well at a wavelength of 405 nm was measured using an ELISA reader.

[0127] Definition of alkaline phosphatase activity unit: In diethanolamine (DEA) buffer at pH 9.8, at 37°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit, also known as one DEA enzyme activity unit. In glycine buffer at pH 9.6, at 25°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit, also known as one Glycine enzyme activity unit. One Glycine enzyme activity unit is approximately equivalent to 3 DEA enzyme activity units. According to the definition of enzyme activity, calculate the alkaline phosphatase activity in the sample and draw a graph respectively.

[0128] Depend on Figure 2 It can be seen that the scaffolds in Examples 1 to 4 of the present invention have a good effect of inducing cells to secrete alkaline phosphatase, but in the case of not using gluconolactone, Comparative Example 1 does not have a gradient pore structure, and its cell activity is not as good as that with a gradient pore structure, which also affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is slightly reduced compared with Example 1. The drug-loaded polydopamine particles in Comparative Example 5 do not contain bioactive ceramics, which also affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is also slightly reduced compared with Example 1. Comparative Example 2 does not contain a ZIF8 layer with good biological activity, and the alkaline phosphatase activity is significantly reduced compared with Example 1. The bioactive ceramic / polydopamine particles in Comparative Example 4 are not drug-loaded, and the alkaline phosphatase activity is also significantly reduced compared with Example 1. Comparative Example 4 does not contain drug-loaded bioactive ceramic / polydopamine particles, and the alkaline phosphatase activity is also significantly reduced compared with Example 1, and its alkaline phosphatase activity is lower than that of Comparative Example 4. Comparative Example 6 contains neither a ZIF8 layer with good biological activity, nor a gradient pore structure and drug-loaded bioactive ceramic@polydopamine particles, and its alkaline phosphatase activity is the lowest.

[0129] 5. Antibacterial performance test of stent

[0130] Take fresh slant cultures of Staphylococcus aureus and Escherichia coli, count the live bacteria in the bacterial suspension, and prepare a diluent (1% peptone in 0.03 mol / L PBS (pH = 7.2-7.4)) to a bacterial count of 5 × 10 5 ~10×10 6cfu / mL of bacterial suspension. Place the samples in sterile plates, add 50μL of bacterial suspension to each sample, record the time of adding bacteria to each tube, inoculate the blood plate 60min after adding bacteria, and place the samples in a 5mL nutrient broth tube. Incubate the blood plate and broth tube inoculated with bacteria at 37℃ for 48h, observe the preliminary results, and continue to culture in the sterile growth tube until the 28th day. If the broth tube is turbid and the blood plate has bacterial growth, it is recorded as positive, indicated by (+); if it is still clear on the 35th day, it is considered as sterile growth, indicated by (–).

[0131] Table 3 Antibacterial effect of the stents prepared in the examples and comparative examples

[0132]

[0133] As shown in Table 3, the composite scaffolds prepared in Examples 1 to 4 of the present invention and Comparative Examples 1, 3, 4, and 5 all have good long-term antibacterial effects and can grow aseptically for 35 days. Comparative Examples 2 and 6 do not contain ZIF8 and have no antibacterial effects.

[0134] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A modified polylactic acid-glycolic acid copolymer composite material bracket, characterized in that: The invention comprises a polylactic acid-glycolic acid copolymer matrix, wherein the surface of the polylactic acid-glycolic acid copolymer support matrix is ​​loaded with a metal organic framework material, and the interior of the metal organic framework material is loaded with an antibacterial drug; the surface and interior of the polylactic acid-glycolic acid copolymer support matrix are distributed with interconnected pores, and the pores gradually increase from the surface to the interior of the polylactic acid-glycolic acid copolymer support matrix; drug-loaded materials are distributed in the polylactic acid-glycolic acid copolymer support matrix, and the drug-loaded materials include ceramic materials and drugs for promoting tissue regeneration and repair, and the surfaces of the ceramic materials and the drugs for promoting tissue regeneration and repair are coated with polydopamine.

2. The modified polylactic acid-co-glycolic acid composite material bracket according to claim 1, characterized in that: The surface of the polylactic acid-glycolic acid copolymer composite material has holes with a size of 1-100 μm.

3. The modified polylactic acid-co-glycolic acid composite material bracket according to claim 1, characterized in that: The ceramic material is selected from at least one of hydroxyapatite, bioglass, calcium silicate, calcium carbonate, calcium sulfate, tricalcium phosphate, octacalcium phosphate, and amorphous calcium phosphate.

4. The method for preparing the modified polylactic acid-co-glycolic acid composite material stent according to any one of claims 1 to 3, characterized in that: The steps include: S1. Mixing the drug-carrying material, gluconolactone and polylactic acid-co-glycolic acid in a solvent to obtain a mixed solution, transferring the solution to a mold and placing the solution for a period of time to obtain a mixed material film; using the mixed material film as a printing material, 3D printing to obtain a stent with a gradient pore structure; After printing, the scaffold with gradient pore structure was immersed in water to remove gluconolactone and residual solvent; S2. Reacting the scaffold with a gradient pore structure, 2-methylimidazole and a zinc source in water to obtain the modified polylactic acid-glycolic acid copolymer composite material scaffold.

5. The method for preparing the modified polylactic acid-co-glycolic acid composite material stent according to claim 4, characterized in that: The preparation method of the drug-carrying material comprises the following steps: dispersing a drug for promoting tissue regeneration and repair and a ceramic material in an aqueous solution containing dopamine, and performing a mixing reaction to obtain the drug-carrying material.

6. The method for preparing the modified polylactic acid-co-glycolic acid composite material stent according to claim 4, characterized in that: The mass ratio of the drug-carrying material to the polylactic acid-glycolic acid copolymer is (0.005-0.05):

1. And / or, the mass ratio of the gluconolactone to the polylactic acid-glycolic acid copolymer is (0.5-3):

1.

7. The method for preparing the modified polylactic acid-co-glycolic acid composite material stent according to claim 4, characterized in that: The process conditions of the 3D printing meet at least one of the following: a) 3D printing uses a printing needle with a diameter of 0.15-0.4mm; b) Printing and heating temperature: barrel 60~80℃, needle 60~90℃; c) Fiber spacing 0.8mm×0.8mm; printing speed 8~17mm / s; d) Air pressure is 320-400Kpa; e) The height of the stent layer is 75-95% of the needle diameter.

8. The method for preparing the modified polylactic acid-co-glycolic acid composite material stent according to claim 4, characterized in that: In step S1, the mixing time is 30-100 hours; And / or, the placement time is 40-100h.

9. The method for preparing the modified polylactic acid-co-glycolic acid composite material stent according to claim 4, characterized in that: The mass ratio of the 2-methylimidazole to the zinc source is (18-60):1; And / or, the zinc source is zinc nitrate.

10. Use of the modified poly(lactic acid-co-glycolic acid) composite material scaffold according to any one of claims 1 to 3 in the preparation of products for promoting bone tissue repair and regeneration.

Citation Information

Patent Citations

  • Medicine carrying modified mesoporous hydroxyapatite biomedical composite material suitable for 3D printing, preparation method and application of medicine carrying modified mesoporoushydroxyapatite biomedical composite material

    CN110420357A

  • Polyester-based microsphere containing drug-loaded calcium-containing inorganic matter as well as preparation method and application of polyester-based microsphere

    CN115804866A

  • 3D printing bio-ink for bone defect repair as well as preparation method and application of 3D printing bio-ink

    CN118252979A

  • Injectable calcium phosphate cement comprising gluconodelta- lactone

    WO2013077739A1

Cited By

  • Polylactic acid coated paper capable of being composted at home and manufacturing process of polylactic acid coated paper

    CN120367082A

  • A nanoparticle, its preparation method and application

    CN122664963A